Direct selling: consumer profile, clusters and satisfaction - Alturas, B.; Santos, M-C. (European Retail Research, 2009)
This study examines the determinants of customer choice of direct selling and satisfaction of the consumer. We obtained survey data for 378 Portuguese consumers and carried out a hierarchical cluster and a logit analysis to assess the buyers’ profile, choice criteria and satisfaction. We found that the profile pattern influences the level of direct selling preference and satisfaction. The results led to identification of three specific clusters and confirmed the importance of the buyer’s experience with this way of shopping. The interactive nature of direct selling renders the customer highly permeable to the salesperson’s influence. These findings contribute to a better understanding and prediction of post-consumption behaviour.